Rapid isolation of lysosomal membranes from cultured cells - Mušálková, D; Lukáš, J; Majer, F; Hřebíček, O; Svobodová, E; Kuchař, L; Honzíková, J; Hůlková, H; Ledvinová, J; Hřebíček, M (Folia biologica, 2013)
We present a simple method for enrichment of lysosomal membranes from HEK293 and HeLa cell lines taking advantage of selective disruption of lysosomes by methionine methyl ester. Organelle concentrate from postnuclear supernatant was treated with 20 mmol/l methionine methyl ester for 45 min to lyse the lysosomes. Subsequently, lysosomal membranes were resolved on a step sucrose gradient. An enriched lysosomal membrane fraction was collected from the 20%/35% sucrose interface. The washed lysosomal membrane fraction was enriched 30 times relative to the homogenate and gave the yield of more than 8%. These results are comparable to lysosomal membranes isolated by magnetic chromatography from cultured cells (Diettrich et al., 1998). The procedure effectively eliminated mitochondrial contamination and minimized contamination from other cell compartments. The enriched fractions retained the ability to acidify membrane vesicles through the activity of lysosomal vacuolar ATPase. The method avoids non-physiological overloading of cells with superparamagnetic particles and appears to be quite robust among the tested cell lines. We expect it may be of more general use, adaptable to other cell lines and tissues.
Keywords: intracelulární membrány; Subcellular Fractions; HeLa Cells; Intracellular Membranes; Lysosomes; Blotting, Western; HEK293 Cells; lyzozomy; subcelulární frakce; Centrifugation, Density Gradient; lidé; HeLa buňky; adenosintrifosfát; HEK293 buňky; western blotting; kyseliny; Adenosine Triphosphate; centrifugace - gradient hustoty; frakcionace buněk; glukosylceramidasa; Acids; Glucosylceramidase; Cell Fractionation; Humans